Migration and university education: An empirical (macro) link - Şule Akkoyunlu; Gil S. Epstein; Ira N. Gang (Bar-Ilan University, Department of Economics, 2022)
Distinguishing between short-run and long-run outcomes we provide new insight into the relationship between education and migration. We examine the specific link between the acquisition of high levels of human capital in the form of university education in Turkey and migration to Germany. We implement bounds testing procedures to ascertain the long-run relationships with the variables of interest in a migration model. Although the bounds testing procedure has advantages compared to other methods, it has not been widely implemented in the migration literature. We find a negative and decreasing non-linear long-run and short-run relationship between home country university education and Turkish migration to Germany over 1970-2015. Over the long run, increased higher education reduces emigration flows.
Keywords: C22; F22; F63; I25; I26; O15; 330; Education; Migration; Turkey; Germany